Salting-out assisted liquid–liquid extraction with dansyl chloride for the determination of biogenic amines in food - Francisco, Karen C. A. [UNESP]; Brandão, Pedro F.; Ramos, Rui Miguel; Gonçalves, Luís Moreira; Cardoso, Arnaldo A. [UNESP]; Rodrigues, José António (Oxford University Press (OUP), 2020)
Biogenic amines (BAs) are compounds present in foodstuff of animal origin that not only can be harmful to the consumer but can also serve as indicators of the product's edibility status. However, BAs’ analysis is rather complicated. Derivatisation methods have been employed to make their analysis less challenging. Salting-out assisted liquid–liquid extraction (SALLE) was herein applied to decrease time that the derivatising agent dansyl chloride (DNS-Cl) requires to be effective. DNS-Cl derivates were separated and analysed by high-performance liquid chromatography with UV and fluorescence detection (HPLC-UV/FD). It was by this way possible to analyse methylamine, dimethylamine, ethylamine, β-phenylethylamine, isopentylamine, putrescine, cadaverine, histamine, tyramine, spermidine and spermine in a straightforward manner in several fish-based and meat-based samples, obtaining results in the order of magnitude of about a few mg per kg. All calibrations curves had r2 higher than 0.99, and limits of detection ranged from 0.0075 to 1.6 mg L−1.
Keywords: Biogenic amines; dansyl chloride; derivatisation reaction; food analysis; high-performance liquid chromatography; low molecular weight amines; salting-out assisted liquid–liquid extraction